Signifikansi Pendampingan Akademisi Dalam Literasi Peradaban Pembangunan Desa Rabak Dalam Dimensi Religiusitas - Aziz, RM; Lusiana, Meiropa; Fuadi, Khairul; Musthofa, Muhammad Wildan (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
A journey to have community development in remote area from Syarif Hidayatullah State Islamic University Jakarta. The unit analysis of this journal is a book with the same tittle published by Pusat Pengabdian kepada Masyarakat (PPM) UIN Syarif Hidayatullah Jakarta 2017. The objective of this study on this article were: the writers was describing the result of KKN program that already held from July 25th, 2017 until August 25th, 2017 in Rabak, Rumpin. However, the writers would like to explain the result of analysis using S.W.O.T analysis into the programs and the result will be described as descriptive qualitative and quantitative method. The results of this study indicate that the community development in village of Rabak has a very rich nature, especially its natural resources to farm, but the wealth that exist in the natural village of Rabak is not in line with its destructive nature management that has existed for a long time.